Modelos en papier maché para la enseñanza de la técnica de la traqueostomía - Moreira Acosta, Gabriel; Jiménez García, Yusleidy; Correa Díaz, Mayelín; Rojas Ampudia, Dr. Luis Alberto; Oriolo Estrada, Dra. Martha A (Universidad Médica Pinareña, 2007)
﻿Abstracto